Prevalence of Leukemia Subtype in the Western Area of Libya: A Focus on Tripoli and Sabratha Cities - Mohamed Abuagela; Abdurraouf Said (Khalij-Libya Journal of Dental and Medical Research, 2024)
Background and aims. Leukemia significantly contributes to the global cancer burden. Research about leukemia types is limited. In this study, we aimed to evaluate the types of leukemia prevalence related to age, gender, and family history in the western area of Libya. Methodology. A cross-sectional study was conducted involving 100 patients who have leukemia. a questionnaire was filled out for each patient. Descriptive statistics for the prevalence of leukemia types were analyzed to assess associating factors including age, gender, and family history. Statistical calculations were performed using the Microsoft Excel Software Version 2010. Results. Of all ages, the highest rate for all leukemia types was age (46 – 65 y) at 29%, however most prevalent leukemia type was CML with 48% of total cases and ALL was the commonest in children (1-10y). Moreover, AML and CLL were the lowest cases. By both genders, male cases were equal to female cases (50% _ 50%). Only 9% of all types have a family history. Conclusion. It is clear, that the most prevalent leukemia type was CML, especially in adults and ALL type was high in children. Only 9% of cases had a family history and by gender the percentage of males to females was equal. Leukemia is a critical cancer that requires further research on associated risk factors. الخلفية والأهداف. يساهم سرطان الدم بشكل كبير في عبء السرطان العالمي. الأبحاث حول أنواع سرطان الدم محدودة. هدفنا في هذه الدراسة هو تقييم أنواع انتشار سرطان الدم المرتبطة بالعمر والجنس والتاريخ العائلي في المنطقة الغربية من ليبيا. طرق الدراسة. أجريت دراسة مقطعية شملت 100 مريض مصاب بسرطان الدم. وتم ملء استبيان لكل مريض. تم تحليل الإحصائيات الوصفية لانتشار أنواع سرطان الدم لتقييم العوامل المرتبطة بما في ذلك العمر والجنس والتاريخ العائلي. تم إجراء الحسابات الإحصائية باستخدام إصدار برنامج Microsoft Excel 2010. النتائج. من بين جميع الأعمار، كان أعلى معدل لجميع أنواع سرطان الدم هو العمر (46 - 65 سنة) بنسبة 29٪، ولكن نوع سرطان الدم الأكثر انتشارًا كان سرطان الدم النخاعي المزمن بنسبة 48٪ من إجمالي الحالات وكان كل ذلك هو الأكثر شيوعًا عند الأطفال (1-10 سنوات). علاوة على ذلك، كانت حالات AML وCLL هي أقل الحالات. ومن كلا الجنسين تساوت حالات الذكور مع حالات الإناث (50% _ 50%). 9% فقط من جميع الأنواع لها تاريخ عائلي. الخاتمة. من الواضح أن أكثر أنواع سرطان الدم انتشارًا هو سرطان الدم النخاعي المزمن، خاصة عند البالغين، وكانت جميع أنواع سرطان الدم مرتفعة عند الأطفال. 9% فقط من الحالات كان لها تاريخ عائلي، وحسب الجنس كانت نسبة الذكور إلى الإناث متساوية. سرطان الدم هو سرطان خطير يتطلب المزيد من البحث حول عوامل الخطر المرتبطة به